Using Inverted Microemulsions for Transdermal Application of Folic Acid - Alkrad, Jamal Alyoussef (Asian Journal of Pharmaceutics (AJP), 2019)
Objectives: This study aimed to improve and assess the transdermal of folic acid through the skin through non-ionic microemulsions (MEs). Methods and Instruments: Eight MEs were developed with different ratios of Span 20-to-Tween 80 and folic acid contents. These MEs were characterized for their droplet sizes, rheological properties. Besides, the encapsulation of folic acid insides the MEs was studied using Fourier-transform infrared spectroscopy. Furthermore, the flux of formulated folic acid in MEs was evaluated using Franz diffusion cell. Results: The MEs showed Newtonian viscosity and droplets sizes <200 nm. However, the droplets sizes increased with increasing Tween 80 and folic acid content. Furthermore, the flux of folic acid related to folic acid concentration. However, using MEs, a high flux of 11.47 ± 6.9 × 10−4 μg/cm2 × h of folic acid through rat’s skin could be achieved. Conclusion: The developed non-ionic MEs containing folic acid can be ideal carriers for administration of folic acid transdermally.